LES INSTRUMENTS DE MUSIQUE AU NIGER. Communication presentee par M. Tolia Nikiprowetsky a la Conference “East and West in Music” (Jerusalem, about 1963) with 19 photographs. (International Library of African Music, 1963)
pages: 57
Keywords: African Music